2005
DOI: 10.1080/13803390490918499
|View full text |Cite
|
Sign up to set email alerts
|

Phonemic Fluency, Semantic Fluency, and Difference Scores: Normative Data for Adult Hebrew Speakers

Abstract: Norms for Hebrew semantic and phonemic fluency were collected in a sample of 369 participants, ranging in age from 18 to 85. Two hundred and sixty nine persons completed both tests and the rest completed only the semantic test. Phonemic fluency was assessed with the use of three letters (bet, gimel, and shin) and semantic fluency with the use of three categories (animals, fruits and vegetables, and vehicles). Scores of individual letters and categories, sum scores, as well as the difference between the semanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
3
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 41 publications
10
117
3
10
Order By: Relevance
“…In contrast, the greater contribution of age in predicting performance in semantic tasks than in phonemic tasks is in agreement with other studies, which suggested that semantic tasks are more sensitive to the effects of ageing (Szatkowska et al, 2000). In addition, there is evidence that different resources of executive functions are necessary to perform semantic VFTs, which activates frontal lobe regions (Kavé, 2005). Other studies confi rmed the effect of age and education on semantic processing (Machado, Correia, & Mansur, 2007), which may justify the interaction between semantic judgment and the other variables.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the greater contribution of age in predicting performance in semantic tasks than in phonemic tasks is in agreement with other studies, which suggested that semantic tasks are more sensitive to the effects of ageing (Szatkowska et al, 2000). In addition, there is evidence that different resources of executive functions are necessary to perform semantic VFTs, which activates frontal lobe regions (Kavé, 2005). Other studies confi rmed the effect of age and education on semantic processing (Machado, Correia, & Mansur, 2007), which may justify the interaction between semantic judgment and the other variables.…”
Section: Discussionmentioning
confidence: 95%
“…As the NeuroTrax battery of tests has not been used extensively in population studies of people with diabetes, the following two well-used short cognitive tests were also included: 1) the digit symbol substitution test, which is a subtest of the Wechsler Adult Intelligence Scale (14) pertaining to a wide array of cognitive domains such as visual motor speed and coordination, capacity for learning, attention, concentration, and short-term memory (it has been extensively used to measure cognitive function in cognitively intact individuals, and its score is well correlated with measures of physical function and future cognitive decline [15,16]); and 2) the verbal fluency test that measures verbal production, semantic memory, and language (17). This test was used in several longitudinal studies, and in each it exhibited an ability to differentiate between people with and without diabetes based on the rate of cognitive decline experienced over time (18,19).…”
Section: Paper-and-pencil Cognitive Testsmentioning
confidence: 99%
“…The number of words generated in 1 min for three different Hebrew letters (bet/b; gimel/g; shin/sh) was timed using a stopwatch. These letters were chosen because they are commonly used in neuropsychological evaluation in Israel [42] . VF scores were achieved by calculating the sum of all words in the lists [42,43] .…”
Section: Assessment Of Cognitive Function and Affectmentioning
confidence: 99%
“…In addition to the MMSE, a screening tool for dementia and general measure of cognitive function, subjects completed several tests of cognitive ability and executive function, including verbal fluency (VF) [42] and forward and backward digit span [43] . In the VF test, subjects were asked to recite out loud words that start with a predefined letter.…”
Section: Assessment Of Cognitive Function and Affectmentioning
confidence: 99%